Bibliometric Study of Scientific Research from 2009 to 2019 on Critical Success Factors and Project Management Performance - Pereira, Geordy Souza; Novaski, Olívio; Santos Neto, Norival Ferreira dos; Souza, Luis Henrique dos Santos Silva; Telles, Francismilton (Revista Gestão da Produção Operações e Sistemas, 2022)
Purpose: This paper seeks to carry out a bibliometric analysis of scientific research available on the Web of Science platform and related to Critical Success Factors (CSF) and project management performance. Theoretical framework: This study is based on concepts related to project management, particularly Critical Success Factors and project management performance. Design/methodology/approach: To conduct this study, scientific publications were retrieved from the database on the Web of Science platform and analyzed. A statistical and content analysis was carried out using the VOSviewer free software and Excel sheets, as well as the WordArt website (www.wordart.com) to create a keyword cloud. Findings: Results show the importance of the subject matter, which was featured in a large number of publications from 2009 to 2019. Engineering sectors are the main areas that deal with it, especially by presenting models, implementing metrics, critical factors, tools and cases, which are used as a basis for performance studies. Data show that partnership networks need creating with greater integration, collaboration, and exchange between publications developed by researchers in Brazil. Originality/Value: By carrying out a bibliometric analysis based on Critical Success Factors and project management development, it is expected to help understanding and the development of studies and the continuous improvement of research into project management, as well as to contribute to the discussion of the quality of scientific research in the field. Keywords: Project management, Critical Success Factors, Project performance, Bibliometrics.O